Biochemical, gas exchange, and chlorophyll fluorescence analysis of maize genotypes under drought stress reveals important insights into their interaction and homeostasis - G.M. SINGH; S. GOLDBERG; D. SCHAEFER; F. ZHANG; S. SHARMA; V.K. MISHRA; J. XU (Photosynthetica, 2022)
Many studies have been conducted on maize to study the effect of drought on yield at the flowering stage, but understanding biochemical and photosynthetic response against drought at the seedling stage needs to be well established. Thus, to understand differential changes and interaction of biochemical and photosynthetic parameters at the seedling stage under drought, a greenhouse experiment with twelve maize genotypes under severe drought (30% field capacity) and irrigated (90-100% field capacity) conditions were performed. Drought differentially altered biochemical and photosynthetic parameters in all genotypes. A sharp increase in hydrogen peroxide, malondialdehyde (MDA), and total antioxidant capacity (TAOC) were seen and a positive association between H2O2 and TAOC, and MDA and transpiration rate (E) was observed under drought. Nonphotochemical quenching increased under drought to avoid the photosystem damage. PCA biplot analysis showed that reducing E and increasing photosynthetic efficiency would be a better drought adaptation mechanism in maize at the seedling stage.